Validation of a reflective practice rubric for evaluating the complexity of teacher candidate digital and written reflections. Issue 3 (4th May 2019) - Rossi, Kirstin; Thorsen, Cathy
ABSTRACT: This study was conducted to validate the effectiveness of a previously published rubric for evaluating the reflective characteristics contained within reflective artifacts. The goal of the study was to test the validity of the rubric when evaluating written reflection and digital artifacts of teacher candidates. The theory of reflection is discussed, and the process of eliciting higher levels of reflection through various modalities from written prompts. Secondly, this study describes the process participants followed while learning to use the rubric, the methods of evaluating artifacts using the rubric, and the results the study produced. The rubric proved to be an effective tool when determining the level of reflection, a teacher candidate demonstrated. Lastly, this article discusses limitations of the rubric, as well as suggestions for further research regarding teaching reflective practices, and how to refine one's own reflective skills to achieve a level of deep reflection on/for action.